Digital Payment: Driven Digital Transformation and Its Impact on Culinary Business Development in Kendari City - Dahniar; Hasriani; Ardiansyah (CV. Vocezmi Learnov, 2025)
This study aims to analyze the impact of e-payment on the development of culinary businesses in Kendari City. This research employs a qualitative descriptive approach, with a specific focus on the use of QRIS as a non-cash transaction tool. Data were collected through observation, interviews, and documentation. The data analysis technique applied in this study follows Miles and Huberman’s interactive model, which consists of data reduction, data presentation, and conclusion drawing. The findings indicate that e-payment contributes significantly to the advancement of culinary businesses in Kendari City and generates positive outcomes. The use of QRIS greatly facilitates transactions between business owners and consumers, as it requires only a single barcode for scanning, making the process more practical and time-efficient. In addition to simplifying transactions, QRIS also supports business owners in recording daily revenues and quickly identifying the products sold.